Tyrosinemia Type 1 – A case report - Islam, Fahmida; Mazumder, Wahiduzzaman; Karim, ASM Bazlul; Biswas, Subir Ananda; Rashid, Rafia; Hasan, Mohammad Shariful; Begum, Fahmida (Bangladesh Journal of Child Health, 2020)
Tyrosinemia Type 1 is a rare inherited metabolic disorder attributable to a deficiency of enzyme fumaryl acetoacetate hydrolase. It has an autosomal recessive pattern of inheritance. It often presents with liver disease or liver failure with predominant bleeding tendencies, Fanconi syndrome and or rickets with neurological crisis. Diagnosis is based on clinical features, increased tyrosine and methionine in plasma and the presence of succinylacetone in urine. Untreated patient develops liver failure, cirrhosis and hepatocellular carcinoma and end stage of renal failure. Here we describe a 9 months old infant presented with massive ascites with hepatosplenomegaly, coagulopathy and hypoalbuminemia. The diagnosis of tyrosinemia type 1 was confirmed based on clinical and biochemical findings. We highlight the need for early diagnosis and initiating treatment at the earliest which improves the quality of life in these patients. Here we report a nine month old male infant presented with abdominal distension, hepatomegaly and ascities diagnosed as Tyrosinemia Type 1. Bangladesh J Child Health 2019; VOL 43 (3) :174-176